Drivers for Development in Regional Higher Education - Sandler, Daniil G.; Sudakova, Anastasia E.; Tarasyeva, Tatyana V. (Economy of Regions, 2020)
Recently, higher education in Russia and abroad has been transformed significantly. Both universities and the state have to tackle challenging and multidirectional tasks. Analysis of theoretical research on the types of higher education institutions and the determining factors provides insights into drivers for development. Simultaneously, multivariate methodology for assessing the state of higher education allows identifying the factors that most affect its transformation. The study demonstrates that these factors depend on the development strategy and economic model of a university as well as government programmes for the development of education and science. One of the major factors affecting the development of regional higher education is the presence of a leading university in the region. This situation is economically justified due to the strong dependence of universities on the federal budget. Moreover, a leading university creates an educational environment for academic staff and students. Their participation in scientific research and academic activities positively influence the development of regional systems. The growing gap between the leading university and other education institutions leads to monopolisation, decrease in competition, and, consequently, decline in performance. Thus, there is a need for structural changes. The particular factors affecting the development of the higher education are the indicators of academic activity and student performance. The conducted analysis suggests the intensification of the trends, indicating further differentiation of regional higher education system with a simultaneous improvement of individual universities in research and development. Additionally, it is necessary to examine the feasibility of structural adjustment within regional systems due to the growing imbalances in development.